A comparative study between ferrous carboxy maltose and iron sucrose in the management of post-partum anaemia in tertiary care hospital - Garag, Seeta Sunil; Kumar, Sanjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Anaemia is a global public health problem contributing tremendously to maternal morbidity and mortality. It is the most common indirect cause of maternal mortality. Variety of injectable iron preparations are now available which can be effective tools for combating post-partum anaemia. This study aims to compare FCM (Ferrous carboxy maltose) and iron sucrose in the treatment of iron deficiency anaemia in post-partum women at KIMS, Hubli, Karnataka, India. Methods: This study was conducted at KIMS, Hubli in the year 2018-19 wherein 100 post-partum women with hb levels ranging from 5-10g% were selected for the study and randomly allocated into 2 groups- FCM group and iron sucrose group. They were administered 1g of FCM and 1g of iron sucrose respectively after clinical evaluation and baseline measurement of hb. They were followed up after 2 weeks for repeat hb% and review of signs and symptoms. FCM and iron sucrose were compared in terms of their efficacy. Results: The mean increase in hb% was found to be 3.2 g% in the FCM group and 2 g% in the iron sucrose group. FCM was also found to be more efficacious in providing relief of common signs and symptoms like easy fatigability and pallor compared to iron sucrose. Conclusions: Ferrous carboxy maltose was found to be more efficacious compared to iron sucrose.